Spatiotemporal strategies to identify aggressive biology in precancerous breast biopsies. Issue 2 (1st October 2020) - Frankhauser, David E.; Jovanovic‐Talisman, Tijana; Lai, Lily; Yee, Lisa D.; Wang, Lihong V.; Mahabal, Ashish; Geradts, Joseph; Rockne, Russell C.; Tomsic, Jerneja; Jones, Veronica; Sistrunk, Christopher; Miranda‐Carboni, Gustavo; et al.
Abstract: Over 90% of breast cancer is cured; yet there remain highly aggressive breast cancers that develop rapidly and are extremely difficult to treat, much less prevent. Breast cancers that rapidly develop between breast image screening are called "interval cancers." The efforts of our team focus on identifying multiscale integrated strategies to identify biologically aggressive precancerous breast lesions. Our goal is to identify spatiotemporal changes that occur prior to development of interval breast cancers. To accomplish this requires integration of new technology. Our team has the ability to perform single cell in situ transcriptional profiling, noncontrast biological imaging, mathematical analysis, and nanoscale evaluation of receptor organization and signaling. These technological innovations allow us to start to identify multidimensional spatial and temporal relationships that drive the transition from biologically aggressive precancer to biologically aggressive interval breast cancer. This article is categorized under: Cancer > Computational Models Cancer > Molecular and Cellular Physiology Cancer > Genetics/Genomics/Epigenetics Abstract : Strategy for high risk assessment.